Determinants of Primary School Teachers’ Health Literacy in Morogoro Municipality, Tanzania: A Reflection on Access to Health Information - David M. Mshingo; Mikidadi I. Muhanga; Raymond J. Salanga; Edwin E. Ngowi (Advances in Public Health)
Background. Teachers have the potential of promoting health knowledge and consequently health-literacy (HL) enhancement. Cognizant of this, interventions geared toward influencing and strengthening school teachers’ HL have remained important. However, for such interventions to be effective, understanding what determines teachers’ HL is inevitable. Purpose. This article analyses the determinants of primary school teachers’ HL by analyzing what prompts their health information-seeking patterns. Methods. A cross-sectional research involving 189 randomly sampled primary school teachers was conducted in 2021 in Morogoro Municipality whereby data were collected through a structured questionnaire survey and analyzed using IBM-SPSS. A score index gauged HL while frequencies and percentages measured other variables. Results. All teachers had high HL with a mean HL (standard deviation) of 8.10062. Only 43.4% searched for HI, 20.1% of those who searched for HI were influenced by health-related problems encountered, 12.2% searched for HI to broaden their knowledge on health-related issues, and 7.4% were prompted by health risks around. Also, 3.7% of the teachers acceded that health-seeking information is influenced by an interest in searching HI for self-health management. About 36.0%, 32.3%, and 31.7% of the teachers agree that the provision of health education, interest to read issues related to HL, and addressing issues related to HL influence teachers’ HL. Conclusion. Teachers have been searching for HI due to different concerns, though there is a need to further enhance such efforts. Recommendation. The government, communities, and development partners should enhance HI seeking to promote teachers’ HL for a healthier society.